2018
DOI: 10.1007/s10827-018-0692-x
|View full text |Cite
|
Sign up to set email alerts
|

Adjusted regularization of cortical covariance

Abstract: It is now common to record dozens to hundreds or more neurons simultaneously, and to ask how the network activity changes across experimental conditions. A natural framework for addressing questions of functional connectivity is to apply Gaussian graphical modeling to neural data, where each edge in the graph corresponds to a non-zero partial correlation between neurons. Because the number of possible edges is large, one strategy for estimating the graph has been to apply methods that aim to identify large spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 65 publications
(114 reference statements)
0
14
0
Order By: Relevance
“…which is a common mask used on in vivo data (Vinci et al, 2018;Yatsenko et al, 2015) as well as in silico experiments following Dale's Law (Chambers et al, 2017;Lin et al, 2017;Lütcke et al, 2013;Pernice and Rotter, 2013;Poli et al, 2016). Like mask M 2 , it only distinguishes null and positive connections, but now it does so without knowledge of sub-population membership.…”
Section: /37mentioning
confidence: 99%
“…which is a common mask used on in vivo data (Vinci et al, 2018;Yatsenko et al, 2015) as well as in silico experiments following Dale's Law (Chambers et al, 2017;Lin et al, 2017;Lütcke et al, 2013;Pernice and Rotter, 2013;Poli et al, 2016). Like mask M 2 , it only distinguishes null and positive connections, but now it does so without knowledge of sub-population membership.…”
Section: /37mentioning
confidence: 99%
“…In previous work we handled the first problem for pairs of neurons using bivariate hierarchical models (Vinci et al, 2016), where pairs of spike counts were assumed to be Poisson with bivariate log-normally distributed latent means; correlation between the latent means can then be thought of as a Poisson de-noised version of spike count correlation. We also handled the second problem, while ignoring the first, by allowing the LASSO penalty to vary with the pair of neurons based on informative covariates (Vinci et al, 2018a), which improved the detection of correct edges and the accuracy of partial correlation estimates. In this paper we combine those two previous strategies to provide a more comprehensive solution.…”
Section: Introductionmentioning
confidence: 99%
“…These covariates are available, but their effects may vary across brain areas, neuron types, and recording techniques. In Vinci et al (2018a) we introduced informative covariate vectors W ij composed of inter-neuron distances and tuning curve correlations to estimate a GGM using a Bayesian λ 1 regularization framework (the graphical LASSO with adjusted regularization, or GAR), where partial correlations between neurons i and j can be penalized differently according to a data driven function of W ij . Through an extensive simulation study we showed that this physiologically-motivated procedure performs substantially better (in terms of correct edge detection and accuracy of partial correlation estimates) than off-the-shelf generic tools, including not only graphical LASSO but also several of its variants that have appeared in the literature, the adaptive graphical LASSO (Fan et al, 2009), the latent variable graphical model (Chandrasekaran et al, 2012), and Bayesian graphical LASSO (Wang, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations